Isotope effect on adsorption diffusivity of water molecules in hydrophobic carbon micropores. (30th October 2020) - Ito, Hiromitsu; Vallejos-Burgos, Fernando; Ono, Yuji; Yoshimoto, Masatsugu; Kaneko, Katsumi; Futamura, Ryusuke; Iiyama, Taku; Matsumoto, Akihiko
Abstract: The fractional filling dependence of corrected diffusivity of H2 O and D2 O confined in activated carbon fiber (ACF) determined using newly developed pressure feedback analysis clearly shows that the adsorption kinetics of H2 O and D2 O on ACF are governed by cluster growth associated with molecular hopping and cluster aggregation. The isotope effect provides an essential influence on the strength of hydrogen bonding, leading to an explicit difference in the adsorption diffusivity during the aggregation process of water molecular clusters at high fractional filling. These results show that the collective dynamic behavior of water molecules in hydrophobic nanospace is governed by the fine balance of hydrogen bonds.